TURKEY: BETWEEN LIBERALISM AND KEYNESIAN REGULATION - (:unkn) unknown (INT ORGANIZATION CENTER ACAD RESEARCH, 2016)
In the final analysis, and despite initial success of Keynesian regulations, years after the 2008 crisis the Turkish economy and society are still in the grip of structural problems of capitalist markets. As recounted below, these factors are chronic high unemployment, vast current account deficits and its associated problems in foreign exchange parities, and persistent inflation. These elements may be triggers for a social or economic crisis at any time and render the country especially vulnerable to external shocks originating in international markets. Hence, it is obvious that Keynesian solutions are not enough to make the system crisis-free.
Keywords: Turkey; Keynesian regulations; Liberalism; FINANCIAL CRISIS